Relationship between cecale microbiota taxa in laying hens with the expression of immune response genes - I. I. Kochish; E. A. Kapitonova; O. V. Myasnikova; M. S. Motin (International Journal of Veterinary Medicine, 2026)
The health and productivity of poultry are largely determined by their gut microbiota. The ceca are an important part of the intestinal tract of birds and are characterized by a unique microbiome capable of influencing key physiological and biochemical processes. This article examines the taxonomic diversity of microorganisms in the ceca of laying hens and their relationship with gene expression in the bird’s organs. Studying the composition of the microbiota and its relationship with gene expression in laying hens’ tissues provides valuable insights into the mechanisms by which the microbiome regulates biological functions and adaptive responses. The aim of this study was to investigate the correlations between the taxonomic diversity of the ceca microbiota and the expression of key immune response genes (AvBD9, AvBD10, IL-8) in laying hens. Sequencing and PCR methods were used for the analysis, which allowed us to identify correlations between specific microbiota taxa and the expression of genes associated with physiological and immune processes. It was found that the microbiota of the ceca of laying hens is characterized by pronounced differentiation in the nature of its relationships with innate immunity genes: a group of taxa that are dominant in the normal state (Actinobacteriota, Bifidobacteriaceae, and the main representatives of Firmicutes) negatively correlates with the expression of AvBD9, AvBD10, and IL8, consistent with their anti-inflammatory and immunoregulatory functions. Conversely, the positive correlations found for the genera Anaerostipes, Romboutsia, and Fournierella indicate their potential to stimulate mucosal immunity, which may be important both for maintaining colonization resistance and for the development of inflammatory responses. These findings have potential applications in optimizing the health and productivity of poultry.